The use of dual number among the youth in Ohcejohka municipality - Sierge Rasmus (Sámi dieđalaš áigečála, 2022)
In this article, I examine how much the use of dual number varies in the colloquial language of young people from Ohcejohka. For the study, I interviewed six young people aged 15–25. As a reference material, I interviewed two people from Ohcejohka who were born in the 1960s, and I collected other reference material from archival sources. I analyzed the use of dual number in subject pronouns, verb inflection, and possessive suffixes. Kejonen (2017) has proposed that the Saami languages have a hierarchy for the dual number similar to the Animacy hierarchy (Corbett 2000). According to Kejonen, in the Saami languages the presence of dual number in personal pronouns is a prerequisite for dual number in finite verb forms, and the dual number must be present in both preceding positions for it to appear in possessive suffixes. In this study, I found that in the adolescent material more than 94 % of the dual subject pronouns were grammatically correct. The same number for the finite verb forms was over 71 % and for the possessive suffixes just over 31 %. There is variation among the informants, but these findings support Kejonen’s proposed dual hierarchy. Even though the dual number has not vanished from any of these idiolects, the numbers show progressively increasing variation when we compare personal pronouns to finite verb forms and then to possessive suffixes.